(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
In the article the morphostructural zoning scheme of the territory of RA is suggested based on quantitative analysis of relief of topographic maps of territory. In the result morphostructural blocks and lineaments of observed territory were highlighted. Juxtaposition of gained results with geological and tectonic data was performed.